2021
DOI: 10.3390/molecules26082236
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis and Applications of ZnO and TiO2 Nanostructures

Abstract: Over the last two decades, oxide nanostructures have been continuously evaluated and used in many technological applications. The advancement of the controlled synthesis approach to design desired morphology is a fundamental key to the discipline of material science and nanotechnology. These nanostructures can be prepared via different physical and chemical methods; however, a green and ecofriendly synthesis approach is a promising way to produce these nanostructures with desired properties with less risk of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 271 publications
(189 reference statements)
1
42
0
1
Order By: Relevance
“…Flavonoids, iridoids, diterpenoids, phenylpropanoids, triterpenoids, and other phenolic compounds detected in phlomis leaf extract may have played a role in nanoparticle formation, according to prior research [30]. Furthermore, as indicated by the foregoing results, the functional groups -OH (hydroxyl), -C=O (Carbonyl), and C-N (amine) found in the leaf extract were definitely implicated in the formation of ZnO NPs [31].…”
Section: Ftir Resultsmentioning
confidence: 71%
“…Flavonoids, iridoids, diterpenoids, phenylpropanoids, triterpenoids, and other phenolic compounds detected in phlomis leaf extract may have played a role in nanoparticle formation, according to prior research [30]. Furthermore, as indicated by the foregoing results, the functional groups -OH (hydroxyl), -C=O (Carbonyl), and C-N (amine) found in the leaf extract were definitely implicated in the formation of ZnO NPs [31].…”
Section: Ftir Resultsmentioning
confidence: 71%
“…In the hunt for new anticancer drugs, there is a significant progress in the fabrication and characterization of tailored metal oxide NPs for the treatment of cancers. Over the last two decades, oxide metallic nanostructures have been continuously designed, evaluated, and used in many applications [12,15,16]. Thereby, various metals (e.g., titanium, silver, zinc) were used to design metallic NPs via synthetic or natural methods, and strengthen the pharmaceutical and medical potential [12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, most of the published studies reported that TiO 2 nanostructures prepared via different physical and chemical routes through bottom-up or top-down approaches (e.g., sol-gel, hydrothermal, solvothermal, hydrolysis, thermolysis, flame, and co-precipitation) [28,29]. These methods were sometimes combined with the principles of 'green chemistry' [15]. However, these synthesis approaches required relatively high temperature pressure, optimization of other parameters (e.g., pH, reaction time) or entail expensive and noxious chemicals, which make such TiO 2 NPs unsuitable for their use as a safe theranostic modality [16,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustainable treatment approaches must consider the approach holistically, beyond the system level. Photocatalyst synthesis has to consider green and sustainable approaches to minimize environmental impact when considering the overall lifecycle of a treatment technology [26][27][28]. In recent decades, conventional metal oxide nanoparticle synthesis methods have relied on the use of hazardous chemicals and solvents plus energy-intensive approaches [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%